Diminished false memory in adults with autism spectrum disorder: Evidence of identify-to-reject mechanism impairment. (January 2018) - Wojcik, D.Z; Díez, E.; Alonso, M.A; Martín-Cilleros, Mª V.; Guisuraga-Fernández, Z.; Fernández, M.; Matilla, L.; Magán-Maganto, M.; Díez-Álamo, A.M; Canal-Bedia, R.; Fernandez, A.
Highlights: Adults with autism produce fewer false memories in a DRM paradigm than controls. In an externalized-free recall people with autism generate fewer words. Adults with autism have problems in using identify-to-reject strategy. Knowledge of memory strategy is spared, but online strategy use is affected. Abstract: Background: Research has demonstrated that memory in individuals with autism spectrum disorder (ASD) is not aided by conceptual relations among words. To explore that, we used a Deese-Roediger–McDermott (DRM) false-memory paradigm, known to rely on associative relations between words. We therefore expected people with ASD in our study to be less susceptible to produce false memories. The novelty of this study was to use the externalized free-recall procedure to further explore the dynamics of correct and error responses in ASD. Method: Adults with ASD and age- and IQ-matched adults in a comparison group were tested on a DRM task where 12 lists of strongly associated words were presented auditorily. At test, an externalized free-recall procedure was used, requesting participants to report presented words, and also any extra words that came to their mind (generated words). Results: As expected, the clinical group produced fewer false memories than the comparison group, potentially due to abnormal relational processing . Moreover, unlike comparison participants, individuals with ASD tended to accept the critical words as belonging to the list rather than as generated, which demonstrates abnormalities in the monitoring capacity underlying an identify-to-reject process. Furthermore, analysis of questionnaires revealed that adults with ASD are less likely than typical adults to use memory strategies at both encoding and retrieval. Conclusions: These findings are discussed in relation to the operation of error-inflating and error-editing mechanisms, both of which seem to be compromised in autism.